Perancangan Lampu Jalan Dengan Panel Surya Terintegrasi Dan Pengaturan Otomatis Intensitas Cahaya - Miftachul Ulum; Khoirul Ogik Saputra; Adi Kurniawan Saputro (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2024)
Indonesia is a country that has a tropical climate and is located on the equator and gets abundant sunlight all year round. So the use of solar energy as an alternative energy is very popular and is starting to be developed in all corners of the country by carrying out a lot of research and testing. In this research, solar cells are used as a source of electrical energy for street lights. The function of these components is SCC (solar charge controller) which regulates and controls the battery charging process, electrical energy is stored in the battery which functions to supply electrical power at night. The inverter functions to change direct current (DC) into alternating current (AC). The photocell sensor functions to regulate the lights, during the day the lights will turn off and turn on at night. There is a passive infrared receiver (PIR) sensor used to detect human presence. This sensor is used to control the light intensity of the lamp, if it is not detected by humans, the lamp will turn on normally. If human presence is detected, the lights will turn on brightly. There is also an automatic solar panel cleaner using a wiper which functions when the solar panels are dirty. The detection method uses current and voltage sensors, when sunlight received by the solar panel and the resulting electric current voltage decreases, the wiper will automatically activate to clean dirty solar panels, thereby maintaining optimal solar panel performance. The solar panel is equipped with a support/pole feature that is designed to go up and down, which makes it easier to use and does not require using a ladder during the maintenance process. The method used in this research is fuzzy. The fuzzy method is used for decision making on wiper conditions. In the research results, the results of this system were obtained from 12 trials of tool measurement results, Matlab simulations, and manual fuzzy logic calculations with a success rate of 91.6%.